Factores determinantes del crecimiento económico ecuatoriano, 1950-2019. - Díaz Kovalenko, Igor Ernesto; De la Cruz, Alex (Universidad Técnica de Machala, 2022)
This paper studies the factors driving the Ecuadorian economic growth through the analysis of three stages of structural changes (1950-1972, 1973-1999, 2000-2017) experimented by the Ecuadorian economy. We perform a statistical growth accounting decomposition to quantify the relative impor-tance of the different factors explaining output growth: inputs accumula-tion (extensive growth) and technological progress (intensive growth). The results obtained confirm the importance that the accumulation in physical capital and employment had played in explaining per capita output growth during the last decades, whereas the contribution of total factor productivity has been more modest.
En este artículo se analizan los determinantes del crecimiento económico ecuatoriano a través del análisis de tres etapas de cambios estructurales (1950-1972, 1973-1999, 2000-2017) experimentadas por la economía ecuatoriana. Se utiliza el método estadístico de contabilidad del crecimiento y se descompone el mismo en dos grupos: acumulación de factores productivos (crecimiento extensivo) y progreso tecnológico (crecimiento intensivo). Los resultados obtenidos confirman que la acumulación de capital físico e incremento del empleo han tenido un papel destacado en los avances en la renta per cápita en las últimas décadas, mientras que la aportación de la productividad total de los factores ha sido más moderada.
Keywords: CRECIMIENTO ECONÓMICO; CONTABILIDAD DEL CRECIMIENTO; PRODUCTIVIDAD TOTAL